Epidemiology, Evaluation and Surgical Treatment of undescended Testis in North Macedonia in the Period from 2011 to 2020 - Memeti, Shaban; Todorovikj, Lazar; Kamiloski, Marjan; Risteski, Toni; Coklevska Shuntov, Natalia; Lumani Bakiji, Njomza; Gjorikj, Sanja (Albanian Society for Trauma and Emergency Surgery, 2023)
Background; Cryptorchidism or undescended testis (UDT) is one of the most common pediatric disorders of the male endocrine glands and the most common genital disorder identified at birth. The main reasons for treatment of cryptorchidism include increased risks of impairment of fertility potential, testicular malignancy, testis torsion, and/or associated inguinal hernia Material and Methods; The aim of this study is to show the epidemical distribution of this pathology in the republic of North Macedonia from 2011-2020 and simultaneously show the number of cases in every city of Macedonia. The number of cases (by city) is shown in Table 1. All data is provided by the archives of The Institute of Public Health, North Macedonia. Discussion: It is very important to find if there is a correlation between the number of undescended testis cases in North Macedonia to the environment, genetics, level of education, level of health care institutions, etc. Reduced hormonal levels, reduced fertility and increased risk of testicular cancer are the most common side effects of no treatment or late treatment. Conclusion; This condition of the undescended testis is very common, and the possible effects of late treatment or no treatment at all are very risky. So, we have to pay attention to the risks in order to try to provide better treatment at the right point of age.
Keywords: undescended testis; epidemiology; treatment